Four cases of bilateral acute retinal necrosis with a long interval after the initial onset. Issue 9 (17th January 2011) - Okunuki, Yoko; Usui, Yoshihiko; Kezuka, Takeshi; Takeuchi, Masaru; Goto, Hiroshi
Abstract : Aims: To report the clinical features and causative virus of bilateral acute retinal necrosis (BARN) with a long interval after the initial onset. Methods: The causative virus and clinical features were retrospectively investigated in four patients with delayed-onset BARN with an interval of more than 3 years after the onset of the disease in the initially affected eye. Results: The intervals between the initially affected eye and the latter affected eye of the four cases were 8 years 7 months, 19 years 3 months, 9 years 7 months and 3 years 6 months. The fourth patient developed a second recurrence in the latter affected eye 17 years 6 months after the initial inflammation in the fellow eye. In all four cases, the same virus species, either varicella-zoster virus or herpes simplex virus, was detected in both eyes by PCR or antibody detection. In all cases, the final best-corrected visual acuity of the latter affected eye (20/20, 18/20, 20/20 and 12/20, respectively) was better than that of the initially affected eye (20 cm hand motion, light perception-negative, light perception-negative and light perception-positive, respectively). Conclusion: The present findings indicate that delayed-onset BARN in the fellow eye was caused by the same herpes virus species that induced the disease in the first affected eye.